KONSEP ZAKAT MENURUT IMAM SYAFI'I TERHADAP DISTRIBUSI DANA BANTUAN SOSIAL - Syamsuri, Syamsuri; Al Muzakki, Nizar Ramadhan (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2025)
Inequality in the distribution of social assistance has become a chronic problem in Indonesia. To overcome this, a more effective mechanism is needed in identifying the most vulnerable groups of people so that assistance is really on target. Imam Shafi'i's thoughts on the distribution of zakat have made a significant contribution. His views on the object of zakat and its distribution mechanism are still very relevant to this day. This study aims to examine the concept of zakat in Imam Shafi'i's thinking and explore its potential application in increasing the effectiveness of the social assistance distribution system. This study uses a qualitative method with a literature study approach. Primary data is obtained from books by Imam Shafi'i, while secondary data comes from various literature related to zakat and social assistance. The findings of the study show that the concept of zakat of Imam Shafi'i emphasizes on principles such as the Principle of Equity (al-'Adalah), the Principle of Adequacy (al-Kifayah), the Principle of Proximity (al-Qarabah), the Principle of Usefulness (al-Maslahah), the Principle of Priority (al-Awlawiyyah), the Principle of Sustainability (al-Istimrariyyah), the Principle of Transparency (al-Syafafiyyah), and the Principle of Convenience (al-Taysir). The principles outlined by Imam Shafi'i can be a guide in designing a social assistance system that is more effective, fair, and in accordance with Islamic values.